Prevalence of severe hypertension in a Sub-Saharan African community - Bamba Gaye; Anne-Laure Janeczek; Kumar Narayanan; Roland N'Guetta; Maxime Vignac; Virginie Gallardo; Xavier Jouven; David Luu; Eloi Marijon (International Journal of Cardiology. Hypertension, 2019)
Background: Though some data from in-hospital or selected populations are available, there are no studies reporting community-level prevalence of Severe Hypertension (SH) in sub-Saharan Africa. Methods: Study participants were recruited within the framework of The Heart Fund's global health initiative. Data were collected in August 2016 from 6 randomly selected sites, ensuring representativeness of both urban and rural areas. Blood pressure (BP) was measured twice, 10 ​min apart, after optimal resting time. SH was defined as systolic blood pressure ≥180 and/or diastolic blood pressure ≥110 ​mmHg ​at both readings. Demographics and data on cardiovascular history/risk factors were collected in the field. Results: Among 1785 subjects examined, 1182 aged between 18 and 75 years were included in this analysis. The prevalence of SH was 14.1% (12.5% females vs 17.0% males; P ​= ​.03) (Fig. 1). Among participants with severe hypertension, 28.9% were either undiagnosed or untreated. Alarmingly, subjects at high cardiovascular risk (age ​≥ ​60 years and/or obese) had even higher prevalence of overall SH (29.6% and 24.9%, respectively) as well as undiagnosed/untreated SH (29.4% and 24.6%). SH prevalence was almost double in urban compared to rural areas (17.0% vs. 9.2%, P ​= ​.02); however, conversely, undiagnosed/untreated SH was significantly higher in rural areas (50.4% vs 21.9%). Conclusion: (s): Our community-based study revealed very high prevalence of SH among adults in Abidjan area, with almost one out of every seven having SH. This underscores SH as a growing public health problem in sub-Saharan Africa.